A darwinian species definition and its implications. Issue 1 (2nd January 2014) - Jolly, Clifford J.
<x xml:space="preserve">Abstract</x> A review of the vast literature on the epistemology and ontology of "species" is far beyond the capacity of both the writer and the length‐allotment of this essay, limiting it to a somewhat dogmatic presentation of personal opinions, few of them original. Also prohibited by the prescribed word limit is an account of species concepts considered but not adopted; in many cases, their omission does not do justice to their intellectual content.